Development of Authentic-Based Assessment Instrument for Biographical Text Materials Based on Material Experts and Design Experts: Pengembangan Instrumen Penilaian Berbasis Autentik Berbantuan Aplikasi Edmodo pada Materi Teks Biografi untuk Siswa Kelas X SMA Swasta Melati - Diana Sri Wahyu Ningsih; Rika Kartika; Sahri Nova Yoga (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
This study aimed to develop and test the feasibility of an authentic-based assessment instrument assisted by the Edmodo application on biographical text material for class X SMA Swasta Melati, based on assessments from material expert validators and design experts. This study used research and development. The development procedure used refers to the development model of Borg and Gall (2003) that has been limited to three stages consisting of introduction, planning, and development. The results of this study indicated that the authentic-based assessment instrument assisted by the Edmodo application in the biographical text material of class X SMA Swasta Melati has met the good category. The assessment of validity level of authentic assessment instruments assisted by the Edmodo application by material experts with an average value as 4.18 indicating a good category and design experts as 4.9 indicating a good category. The assessment of feasibility level and effectiveness of authentic assessment instruments assisted by the Edmodo application by teachers with an average as 4.92 indicating a very good category, and individual trials as 4.86 indicating a very good category, the smallest group trial as 4.83 indicating a very good category, and the limited trial as 4.83 showed a very good category. It can be concluded that the authentically based assessment instrument assisted by the Edmodo application for the biographical text material of class X SMA Swasta Melati is valid and feasible to be used as an authentic assessment instrument assisted by the Edmodo application